2021
DOI: 10.56093/ijans.v91i9.116463
|View full text |Cite
|
Sign up to set email alerts
|

Does Pleurotus ostreatus influence health status and meat quality attributes of broiler chickens?

Abstract: An 8-week study was piloted to establish the effect of Pleurotus ostreatus (PO) extract (Oyster mushroom) on health status and quality attributes of meat. One hundred and eighty (180) day old Cobb chicks were allotted into three treatments and orally administered extract of Pleurotus ostreatus at 0 (control), 2000 and 4000 mg/L. Haematological indices, serum metabolites, quality attributes of meat and oxidative stability of meat were determined. Oral administration of PO had no effect on haematological indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The oral administration of Pleurotus ostreatus at 4000 (mg/L) in water improved the meat quality of Cobb broilers via the improvement of oxidative stability of meat samples through the reduction in thiobarbituric acid reactive substances (TBARs) and increase in the glutathione peroxidase. The sequence of these processes positively stabilizes the meat tissue against lipid oxidation, thereby prolonging the quality of meat and its shelf life [ 124 ].…”
Section: Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The oral administration of Pleurotus ostreatus at 4000 (mg/L) in water improved the meat quality of Cobb broilers via the improvement of oxidative stability of meat samples through the reduction in thiobarbituric acid reactive substances (TBARs) and increase in the glutathione peroxidase. The sequence of these processes positively stabilizes the meat tissue against lipid oxidation, thereby prolonging the quality of meat and its shelf life [ 124 ].…”
Section: Meat Qualitymentioning
confidence: 99%
“…There is clinical proof of significant medicinal properties in species such as Agaricus bisporus , Agaricus blazei , Agaricus sylvaticus , Ganoderma lucidum , Lentinula edodes , Grifola frondosa , Hericium erinaceus , and Pleurotus ostreatus in livestock. The extract of Pleurotus ostreatus in broiler’s water improved growth performance, dressed weight, and reduced the number of pathogenic bacteria in the gut [ 12 , 13 ]. Altop et al [ 14 ] also observed improved feed efficiency with better growth performances and improved intestinal morphology in the broiler fed Agaricus bisporus stalk.…”
Section: Introductionmentioning
confidence: 99%